2014
DOI: 10.1128/mcb.00865-13
|View full text |Cite
|
Sign up to set email alerts
|

Abcb10 Role in Heme Biosynthesis In Vivo: Abcb10 Knockout in Mice Causes Anemia with Protoporphyrin IX and Iron Accumulation

Abstract: Abcb10, member 10 of the ABC transporter family, is reportedly a part of a complex in the mitochondrial inner membrane with mitoferrin-1 (Slc25a37) and ferrochelatase (Fech) and is responsible for heme biosynthesis in utero. However, it is unclear whether loss of Abcb10 causes pathological changes in adult mice. Here, we show that Abcb10 ؊/؊ mice lack heme biosynthesis and erythropoiesis abilities and die in midgestation. Moreover, we generated Abcb10 F/؊ ; Mx1-Cre mice, with Abcb10 in hematopoietic cells dele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 30 publications
3
54
0
Order By: Relevance
“…Mice with one ABCB10 gene removed survived to become adults and were apparently normal, but their hearts were more susceptible to damage by oxidative stress during ischaemia and reperfusion [25]. A recent study using conditional knockouts of the ABCB10 gene in haematopoietic cells showed a dramatic accumulation of protoporphyrin IX (PPIX) in erythrocytes and accumulation of iron inside the mitochondria [53].…”
Section: Abcb10 In Mammalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice with one ABCB10 gene removed survived to become adults and were apparently normal, but their hearts were more susceptible to damage by oxidative stress during ischaemia and reperfusion [25]. A recent study using conditional knockouts of the ABCB10 gene in haematopoietic cells showed a dramatic accumulation of protoporphyrin IX (PPIX) in erythrocytes and accumulation of iron inside the mitochondria [53].…”
Section: Abcb10 In Mammalsmentioning
confidence: 99%
“…In the absence of ABCB10, Mfrn1 (but not Mfrn2) is destabilized and Fe import is decreased. The ABCB10-Mfrn complex also interacts with ferrochelatase, but this interaction is weaker [21] and is not required for ferrochelatase stability [53]. The suggestion that the main role for ABCB10 is to stabilize Mfrn1 is challenged by the observation that there are no conserved regions on the external surface of ABCB10 [6].…”
Section: Abcb10 In Mammalsmentioning
confidence: 99%
“…This interaction ensures that the imported iron is preferentially utilized for heme production. Deletion of Abcb10 in mice impaired heme biosynthesis, erythropoiesis, and caused embryonic lethality [59]. Tissue-specific knockout of Abcb10 in mouse hematopoietic cells resulted in accumulation of iron and PPIX in reticulocytes, confirming its role in the final step of heme synthesis pathway [59].…”
Section: Regulation Of Heme Synthesis Enzymesmentioning
confidence: 98%
“…A study suggested that ABCB10 might mediate this translocating event [60]. However, other biochemical and genetic studies indicate that ABCB10 is more likely to be involved in the final step of heme synthesis, as discussed above [59,61].…”
Section: Transport Of Heme Synthesis Intermediatesmentioning
confidence: 99%
“…ABCB10 physically interacts with MFRN1 and increases the half-life of MFRN1 (Chen et al, 2009). Deficiency of ABCB10 impairs mitochondrial iron import and causes PPIX accumulation (Yamamoto et al, 2014). At the same time, ABCB10 deficiency in mice results in iron accumulation in cytoplasm and leads to sideroblastic anemia (Yamamoto et al, 2014).…”
Section: Disregulation Of Ppix Homeostasismentioning
confidence: 99%